Spectrum of Various Morphological Changes Detected on High Resolution Ultrasound & MRI in Patients with Painful Shoulder - Kumar, Abhay; Bansal , Nikita; Sharma , Madhu (Asian Journal of Medical Radiological Research, 2021)
Background: Shoulder joint pain is one of the most common complaints that are encountered in the Orthopedics and Rheumatology Department. X-Ray, Ultrasound (US) and MRI are widely used in evaluating various shoulder pathologies. US is a simple, cheap, fast and non-invasive imaging technology for detection of rotator cuff and non-rotator cuff pathologies. Currently, MRI is gold standard and more precise for imaging for shoulder joint pathologies. In this study, we are presenting a spectrum of various positive findings in 30 patients, presenting with painful shoulder, studied with HR USG and MRI. Both imaging modalities successfully detected 44 cases of partial tear of SUPRASPINATUS. US imaging yields a sensitivity of 95% and an accuracy of 91%. The corresponding values of MRI were greater than 95%. According to cited studies, USG imaging can be considered almost equally effective in detecting partial tears of the rotator cuff compared to MRI with a sensitivity of more than 90% and accuracy of 90%, particularly located in the SUPRASPINATUS (Small letters Supraspinatus). MRI may be reserved for doubtful or complex cases, in which delineation of adjacent structures is mandatory prior to surgical intervention. Tears of the INFRASPINATUS and subscapularis tendon have always been considered uncommon as compared to the SUPRASPINATUS. We found only 4 cases (14.3%) of IST and 2 cases (6.6%) subscapularis tendon tear. Subjects and Methods: The study was carried out in Radiology department of SNMC on patients with painful shoulder. HRUSG Performed using 7 -18 MHZ linear probe and MRI by 1.5 Tesla Philips machine using Shoulder coil .Various sequences like T1 ,T2 ,PDW ,FSE,FAT suppressed or without Fat suppressed, gradient echo planes in multiple planes. Result: In the present study maximum no of patients with painful shoulder were of Rotator cuff injury that is 20 patients out of total 30 patients .17 patients were of partial thickness tendon tear. 15 of them were diagnosed on HRUSG and all 17 patients were diagnosed on MRI .Full thickness tear was seen 4pts on MRI and 3 patients on USG. Tears/Tendinosis/tendinitis in the tendons were of prevalence Supraspinatous >infrspintous>Subscapularis. Joint effusion was equally diagnosed on HRUSG and MRI. For Hill sachs lesions and Bankarts lesions MRI Is the modality of choice. Conclusion: From present study we could conclude that in patients of painful shoulder HRUSG is a modality of choice for primary work up and diagnosis specially where MRI is not available. However for accuracy and extent of rotator cuff tears /tendinosis MRI is Gold standard so as to guide Orthopedician and Physiotherapist. For follow ups both HRUSG and MRI are helpful.